Pharmacological modulation in mesial temporal lobe epilepsy: Current status and future perspectives. (November 2016) - Gambardella, Antonio; Labate, Angelo; Cifelli, Pierangelo; Ruffolo, Gabriele; Mumoli, Laura; Aronica, Eleonora; Palma, Eleonora
Graphical abstract: Abstract: Mesial temporal lobe epilepsy (MTLE) is frequently associated with hippocampal sclerosis ( Hs ), possibly caused by a primary brain injury that occurs a long time before the appearance of neurological symptoms. MTLE- Hs is, however, a heterogeneous condition that evolves with time, involving both environmental and genetic components. Recent experimental studies emphasize that drugs or drug combinations that target modulation and circuitry reorganization of the epileptogenic networks favorably modify the complex molecular and cellular alterations underlying MTLE. In particular, the link between neuroinflammation, GABAA R and epilepsy has been extensively studied mainly because of the relevant therapeutic implications that the pharmacological modulation of these phenomena would have in the clinical practice. In this review, we briefly summarize the studies that could pave the road to develop new disease-modifying therapeutic strategies for pharmacoresistant MTLE patients. Both clinical observations in human MTLE and experimental findings will be discussed, highlighting the potential modulatory crosstalk between the deregulation of the inhibitory (GABAergic) transmission and the sustained activation of the innate immune response.